Music and consumer behaviour - North, Adrian; Hargreaves, David (Oxford University Press, 2009)
This article begins with a brief overview of two particular effects of music that have received a considerable amount of attention: the effect of music on the speed with which customers behave, and the impact of music on time perception. It then illustrates the many other commercially relevant processes that can be influenced by music. Music can have a wide range of positive commercial benefits. It can influence the places that customers go to, customers' ability to achieve a desired level of arousal, the atmosphere of commercial premises, the amount which customers are prepared to spend, the amount they actually spend, the products they buy, their memory for advertising, and the amount of time they wait on hold. Since music can have many different effects it is important to prioritize those that correspond best with the business's marketing goals. Following from this, there can be no single ‘right’ type of music that is a universal commercial panacea, and the real issue is how to select music which addresses the most important marketing goals and does not hamper others.